Determination of Low Molecular Weight Silicones in Plasma and Blood of Women after Exposure to Silicone Breast Implants by GC/MS - Flassbeck, Daniela; Pfleiderer, Bettina; Grümping, Rainer; Hirner, Alfred V (Analytical chemistry (Washington), 2001)
A sensitive, one-step sample preparation method for detection of volatile, low molecular weight (LMW) cyclic silicones hexamethylcyclotrisiloxane (D3), octamethylcyclotetrasiloxane (D4), decamethylcyclopentasiloxane (D5), and dodecamethylcyclohexasiloxane (D6) in plasma and blood using gas chromatography coupled with mass spectrometry (GC/MS, SIM mode) is presented. In spiked experiments, extraction efficiencies for these siloxanes (100−20 000 ng/mL) were approximately 90% for plasma and approximately 80% for blood; only in the case of D3 was the recovery very low. Plasma and blood of women who are or were exposed to silicone gel-filled implants and of control subjects were analyzed for low molecular weight silicones. D3−D6 were not detectable in control plasma or blood. Although the investigated numbers of patients samples are very limited, and thus, no statistical analysis is possible, our data clearly show a general increase in the amount of LMW cyclic siloxanes in the bodies of women with silicone implants. In particular, several years after ruptured silicone implants were removed, siloxanes could still be found in blood samples from several women. Siloxane compound D3 varied between 6 and 12 ng/mL (plasma) and between 20 and 28 ng/mL (blood), whereas the concentration range of D4 was 14−50 ng/mL (plasma) and 79−92 ng/mL (blood). D5 and D6, with one exception, could not be detected.